Behavioral Approach Using Shaping Techniques to Increase the Responsibility of Late Student Students in Islamic Boarding Schools - Heri Fadli Wahyudi; Evadatul Hasanah (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
Being late is deviant behavior by not arriving on time which violates the established rules. which, if left unchecked, will have a negative impact on the development and learning achievements at the boarding school, can disturb other students, and make individuals inconsistent in all things, as well as making students irresponsible. The problem raised in this research is how to apply shaping techniques at the Baitul Atiq Islamic boarding school, Karduluk Village, Pragaan District, Sumenep Regency to increase responsibility and minimize the occurrence of late behavior, which is described in two focuses, namely: 1. How is the counseling process using shaping techniques to increase responsibility answered the female student late at the Baitul Atiq Islamic boarding school. 2. What is the impact of applying shaping techniques to increase the responsibility of late female students at the Baitul Atiq Islamic boarding school. Data collection was carried out using observation, interviews and documentation methods. The data analysis used is triangulation. This research uses a descriptive qualitative method with a case study approach because the researcher will investigate cases of late behavior and will provide direct treatment through counseling with shaping techniques. The results of this research are the counseling process using shaping techniques applied at the Baitul Atiq Islamic Boarding School in Karduluk Village, namely by setting an alarm on the alarm clock when getting ready and providing reinforcement when the desired behavior appears. According to researchers, shaping techniques are effective because they can lead to positive changes.